Advancing circular economy approaches in plastic waste management: a systematic literature review in developing economies - Mohammad Ramli, Abu Hanifah; Abd Manaf, Latifah; Zulkeflee, Zufarzaana; Andriyono, Sapto (Elsevier B.V., 2024)
Global plastic pollution is a major environmental problem, and regions with developing economies have particular obstacles in properly managing plastic waste. Despite growing awareness of the need for sustainable solutions, research on implementing circular economy principles in plastic waste management remains insufficient, especially in the developing economies. In response to this research gap, this study aims to conduct a systematic literature review focusing on circular economy strategies for plastic waste management in developing economies. The current research employed a synthesis of various research methodologies, adhering to the ROSES (RepOrting standards for Systematic Evidence Syntheses) publication standard. Utilizing a systematic approach, this study identified relevant articles from two primary online databases, Scopus and Science Direct. Four (4) main themes where identified, namely (i) the Circular Economy Strategies; ii) Policy and Regulation; iii) Community Engagement and Awareness; and lastly; iv) Technological Innovations and sub-divided into another eleven (11) sub-themes. In the end, sixteen (16) articles were meticulously selected and thoroughly analyzed to provide an in-depth comprehension to meet the study's objectives. For future study recommendations, it is suggested for scholar to integrate Policy and Regulation with Circular Economy Strategies in developing economies, include region-specific studies to understand local challenges and solutions, and conduct longitudinal research to evaluate the long-term environmental, economic, and social impacts of circular economy strategies implementation at which will benefits the people from the developing economies regions.